An Ecological Discourse Analysis of COVID-19 Speech by Dr Tedros on World Health Organization YouTube Channel - Haris, Arkin (STKIP Yapis Dompu, 2022)
Ecological crisis increases into the biggest current issue since COVID-19 pandemic hit the world. The awareness and perception about the relationships between environment and other organisms has moved slowly. Meantime, the ecological terminology is developing as extraordinary topic to discuss in all aspects because has had a major effect on our live. As a new transdisciplinary paradigm formed by the combination of ecology and linguistics, ecolinguistics principally studies the influence of language use on human beings, nature and other organisms. This paper essentially uses transitivity of systemic functional linguistics theory proposed by Halliday to analyze the ecological discourse of COVID-19 speech by Dr Tedros in World Health Organization (WHO) YouTube Channel. Therefore, the ecological philosophy of this paper explores from the theory of Ecological Philosophy that addresses our understanding, as part of the environment in which we live, and how we learn and act on environmental issues. Present research employed qualitative, descriptive method containing observation. Results revealed ecological discourse analysis of transitivity system theory can be used in shedding light on use of language in this speech to invigorate the perception by understanding based on the three ecologies, there are environment, social relations and human (mental) subjectivity. Furthermore, on mood system analysis, this speech consists of larger number of declarative moods and some interrogative moods. In summarization, finding of current study will deliver a theoretical foundation of ecological discourse analysis for future researchers in the field.